Analisis Kemampuan Literasi Sains Siswa Di Kecamatan Batangtoru - Harahap, Aminah; Lubis, Ainun Mardiyah (Institut Agama Islam Negeri Padangsidimpuan, 2025)
This research was motivated by the low level of students' scientific literacy which is one of the educationalproblems in Indonesia with the average achievement of scintific literacy scores being still low. The aim of the research is to determine the scientific literacy abilities in the competency aspect, knowledge aspect, context aspec and attitude aspect of high school students in Batangtoru District. This assesment is based on the Program for International Student Assessment (PISA) standars. The method used is a quantitative approach. The subjects of this research consisted of 92 students in Batangtoru sub-district. The instrument used is a written test in the form of a description to determine scientific literacy abilities based on threeaspects (competence, knowledge and context). An average percentage of 27.45% was obtained in the verypoor category. Then, to assess aspects of attitude, the instrument, used is a non-test, namely in the form of a questionnaire. Obtained an average percentage of 73.49% in the good category.